- #1

- 140

- 0

let's see, i can convert that to (8x^2)/(x^(1/2))

but i dont see how it is the same as 8x^(3/2)... can someone lend me a hand?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter ProBasket
- Start date

- #1

- 140

- 0

let's see, i can convert that to (8x^2)/(x^(1/2))

but i dont see how it is the same as 8x^(3/2)... can someone lend me a hand?

- #2

cepheid

Staff Emeritus

Science Advisor

Gold Member

- 5,192

- 38

It's simply the laws of exponents: when you divide two powers with the same base, you simply subtract the exponents:

x^{2} / x^{1/2}

= x^{ 2 - 1/2 } = x^{ 4/2 - 1/2 } = x^{3/2 }

In general, when you multiply, add the exponents. When you divide, subract the exponents, When you raise the power to another power, multiply the exponents. Notice that for positive integer exponents, these laws are very easy to understand: x cubed times x squared is three x's multiplied together times two x's multiplied together. How many x's are there multiplied together in total at the end? Five. And if you had added the exponents: 3+2 =5.

Even in this example, it's pretty easy to understand: consider this:

[tex] (\sqrt{x})^2 = x [/tex]

Therefore: [tex] x^2 = (\sqrt{x})^2 \cdot (\sqrt{x})^2 = (\sqrt{x})(\sqrt{x})(\sqrt{x})(\sqrt{x}) [/tex]

Therefore: [tex] x^2 / x^{1/2} = \frac{(\sqrt{x})(\sqrt{x})(\sqrt{x})(\sqrt{x})}{\sqrt{x}} = (\sqrt{x})(\sqrt{x})(\sqrt{x}) = (x^{1/2})^3 = x^{3/2} [/tex]

As far as I know, the laws hold for any real exponents, positive or negative.

x

= x

In general, when you multiply, add the exponents. When you divide, subract the exponents, When you raise the power to another power, multiply the exponents. Notice that for positive integer exponents, these laws are very easy to understand: x cubed times x squared is three x's multiplied together times two x's multiplied together. How many x's are there multiplied together in total at the end? Five. And if you had added the exponents: 3+2 =5.

Even in this example, it's pretty easy to understand: consider this:

[tex] (\sqrt{x})^2 = x [/tex]

Therefore: [tex] x^2 = (\sqrt{x})^2 \cdot (\sqrt{x})^2 = (\sqrt{x})(\sqrt{x})(\sqrt{x})(\sqrt{x}) [/tex]

Therefore: [tex] x^2 / x^{1/2} = \frac{(\sqrt{x})(\sqrt{x})(\sqrt{x})(\sqrt{x})}{\sqrt{x}} = (\sqrt{x})(\sqrt{x})(\sqrt{x}) = (x^{1/2})^3 = x^{3/2} [/tex]

As far as I know, the laws hold for any real exponents, positive or negative.

Last edited:

- #3

- 740

- 13

- #4

Hurkyl

Staff Emeritus

Science Advisor

Gold Member

- 14,916

- 19

For negative or complex bases, or complex exponents, this property fails fairly often -- you should generally try not to apply it to them.

Share: